Scalable copper‐catalyzed preparation of imidazopyridinones from iodopyridinyl ureas. (7th November 2022) - Rugg, Kyle W.; Balk, Regina C.; Paolillo, Joshua M.; Yerkozhanov, Dauzhan; Tampone, Thomas G.; Holan, Martin; Buono, Frederic G.; Reeves, Jonathan T.
Abstract: The efficient copper‐catalyzed construction of imidazopyridinones is described. Beginning from iodopyridinyl ureas, Ullmann coupling provides imidazopyridinones in good yield. Manufacturing by this process is described on 473 kg scale; the scope and limitations of substrates is also detailed. Abstract : The efficient copper‐catalyzed construction of imidazopyridinones is described. Beginning from iodopyridinyl ureas, Ullmann coupling provides imidazopyridinones in good yield. Manufacturing by this process is described on 473 kg scale; the scope and limitations of substrates is also detailed.